Parsing the urban poverty puzzle: A multi-generational panel study in Rio de Janeiro's favelas, 1968 - 2008 - Janice E. Perlman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2010)
This paper describes the methodology of a longitudinal multi-generational study in the favelas (shantytowns) of Rio de Janeiro from 1968 to 2008. Major political transformations took place in Brazil during this interval: from dictatorship to 'opening' to democracy; major economic transformations from 'miracle' boom to hyperinflation and crisis, and to relative stability; and major policy changes from the removal of favelas to their upgrading and integration. However, despite the cumulative effects of these contextual changes, poverty programmes and community efforts, the favela population has continued to grow faster than the rest of the city and the number and size of the favelas has consistently increased over these decades.
Keywords: O18; R21; R23; N96; 330; urbanization; Brazil; poverty; community; slums